Effect Combination of Inspiratory Muscle Training and Aerobic Exercise on Cardiopulmonary Endurance and Pulmonary Function in Systemic Lupus Erythematosus - Irsan Agung Ramdhani; Irma Ruslina Defi; Dian Marta Sari; Rachmat Gunadi Wachjudi (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease which decreasedcardiopulmonary endurance and pulmonary function are the clinical manifestations. Inspiratory MuscleTraining (IMT) has never been studied before, but aerobic exercise is commonly studied in SLE patients.This study was conducted to know the combination ef fect of IMT and aerobic exercise in SLE patients.Materials and methods: This study use quasi experimental design with pre and post-test approach.Fourteen SLE patients that included in the Lupus Low Disease Activity State (LLDAS) were givenIMT and aerobic exercise for 8 weeks. Cardiopulmonary endurance is measured by 6-minute walk test(6MWT) and Metabolic Equivalents (METs), pulmonary function by Maximal Inspiratory Pressure(MIP), Forced Expiratory Volume in 1 second (FEV1), and Forced Vital Capacity (FVC).Results: There is significant increase in pre and post intervention data, 397.45 ± 49.34 vs 427.50 ± 48.67for 6MWT; 5.25 ± 1.14 vs 5.84 ± 1.08 for METs; 56.20 ± 14.24 vs 86.36 ± 20.73 for MIP; 68.00 ± 10.71vs 72.90 ± 11.30 for FEV1; and 1.81 ± 1 1.14 vs 77.36 ± 11.80 for FVC.Conclusion: The combination of IMT and aerobic exercise can increase cardiopulmonary endurance andpulmonary function in SLE patients.Keywords: aerobic, inspiratory muscle training, lupus low disease activity state, maximal inspiratorypressure, metabolic equivalents, six-minute walk test.